Measurement Of Organic Concentration in Aldehydes By The Derivative Neutron Activation Analysis Technique - AL-Munem, D.A.; Hussein, B.J.; AL- Jabbar, H.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is determine the concentration of the organic oxygen in some organic compounds (Aldehydes ) by the derivative neutron activation analysis technique, and the derivative of the oxygen by the nitrogen equivalent toit and the irradiation of anew sample in flounce (1.73*106 n.cm-2.s-1) by the neutron generator .Then the calculation of the radioactivity which is done by using NaI(Tl) . After that we determine the concentration of nitrogen by calibration curve that includes nitrogen compounds which have apparent chemical and physical characteristics .For comparison the result is done by using keldal method.